Influence of number and position of porcelain specimens in the furnace on flexural strength and translucency - Machado, Pablo Soares; Camponogara, Jeanni Gonçalves; da Silva Rodrigues, Camila [UNESP]; Jacques, Letícia Borges; Valandro, Luiz Felipe; Rippe, Marília Pivetta (Universidade Estadual de Campinas, 2022)
Aim: The aim of this study was to investigate the influence of the quantity and positioning of feldspathic ceramic specimens inside the furnace on their flexural strength and translucency. The tested hypotheses were that the arrangement of specimens in the furnance would not influence 1) the translucency or 2) the biaxial strength of the porcelain. Methods: Ninety porcelain specimens were made (1.2 mm thickness and 13.5 mm diameter) and assigned into two main groups (n=15): G1 group - 15 firing cycles containing only one specimen each, always at the center of the refractory; and G5 group - 15 firing cycles containing five specimen each, where one specimen was at the center of the refractory and four specimens positioned equidistantly on the periphery. The translucency test was performed using a spectrophotometer, followed by the flexural strength test, according to ISO 6872:2015. T-student test was performed for both the mechanical and optical obtained data. Results: The flexural strength of the porcelain was not affected by the positioning (center x periphery) of the specimens inside the furnace (p =0.08), but the translucency was affected (periphery > center; p =0.009). Regarding to the number of feldspathic ceramic specimens, the biaxial flexural strength was affected (p =0.025), as well as the translucency (p <0.05). Conclusion: A higher quantity of feldspathic ceramic specimens for each firing cycle decreased its biaxial flexural strength and translucency. Also, specimens positioned at the center of the refractory became less translucent than those positioned at the periphery.
Keywords: Dental porcelain; Flexural strength; Optical phenomena